Can we trust AI to generate agricultural extension advisories? - Koo, Jawoo (CGIAR System Organization, 2023)
Agricultural extension services play a crucial role in supporting 570 million small-scale farmers worldwide, contributing to food security and rural development through the dissemination of technical advice and best practices. These vital services, however, often face significant challenges, including weak institutional capacity, inadequate reach, and limited access to up-to-date scientific knowledge. Language is also a significant barrier. Advisories only provided in the world’s dominant languages cannot easily be understood in local communities with minor languages and dialects. Many information and communication technologies have been piloted to address these systemic challenges, such as videos,short message services, and interactive voice response services. And, what about artificial intelligence (AI) chatbots?